HUBUNGAN BODY CONDITION SCORE (BCS) DENGAN SERVICE PER CONCEPTION (S/C) PADA TERNAK DOMBA DI KABUPATEN LANGKAT - Kurniawan, Media Agus; Sitepu, Sukma Aditya; Aditya, Gilang (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2023)
An essential factor in the success of a sheep breeding business is the sheep's body condition. Sheep with a low Body Condition Score (BCS) will make it difficult for the lamb to mate and fertilize due to lack of nutrition. Sheep with a Body Condition Score (BCS) that is too high will also make it difficult for the sheep to reproduce due to fat deposits in the reproductive tract. This study aims to determine the relationship between Body Condition Score and the reproductive performance of sheep in Langkat Regency with Service Per Conception (S/C). The material used was 50 sheep in Langkat Regency. The method used in this research is a case study, namely by collecting primary and secondary data. The observed variables are Body Condition Score (BCS) and Service per Conception (S/C). The study results show that the regression equation relates to Body Condition Score (BCS) and Service Per Conception (S/C) Y=2.828-0.339X. (R2) 6.9%. (r) 0.263. In conclusion, the relationship between Body Condition Score (BCS) and Service Per Conception (S/C) is positive, with an R2 = 6.9%.